Strategies matrimoniales et appropriation de la terre chez les Yansi.: Pour une grande solidarité entre generations - Moke Key, Willy-Roland Mfukala (Afrika Focus, 1994)
A weak concentration of landowner system is among the main properties of African people specially those in the South of Sahara. To have acces to land is a question which concerns above all the level of rationalisation than that of true distribution. This paper deals with the strategies of both landowner system and marriage settlement in the Yansi society. The Yansi people are living in the Kinzwene area specially in the constituency of Bagata in the province of Bandundu of Zaïre country. These people have opted for a marriage settlement based on matriarchy. With reference to Bohanman’s methodes of conception to write down this paper, we have proceeded by confrontation of these methods to the Yansi social reality. From this we can say: the land appropriation and the one af a woman (as spouse) are from a system of affectation to using things but not from the right to have it used according to the european common law which is based on the former roman law. Only one adage rules the both landowner and marriage settlement strategies: "NSO MPE NGUL M’WAG" (if a cassava field is left, it is given to wild boars). This maxim brings a reply to the women moving, the fields and the properties regime inside the same linear system or in the archilinear one. According to Yansi people, landowner system is a question which concerns at the same time the economic, the social and cultural aspects. What is called "formal marriage " (Ukwel Kituiil) is a kind of marriage settlement strategyboth social and temporal. Tlie Yansi landowner system and marriage settlement are to be seen as a way tot remain interdependent from generations to others.